An applied framework to assess exploitation and guide management of coral‐reef fisheries. Issue 3 (16th March 2017) - Houk, Peter; Tilfas, Ronny; Luckymis, Marston; Nedlic, Osamu; Ned, Bruno; Cuetos‐Bueno, Javier; McLean, Matthew
Abstract: Coral‐reef fisheries pose a problem for traditional forms of management because stock assessments and demographic data are limited in diverse systems. We used catch records coupled with fisher interviews to derive hierarchical indicators of fishery status by (1) characterizing catch‐and‐effort trends with respect to environmental factors, (2) assessing the degree to which biomass‐and‐abundance distributions were coupled across trophic levels, and (3) identifying key characteristics of species‐based landings that were sensitive to fishing pressure and linked with management guidance. Using data across one year from a representative Pacific Island fishery, we show that catch and effort were constrained by environments, as both were disproportionally highest during favorable new moon phases in spring, but more effort was required to catch fewer fish later in the year, and the size of target species declined. The magnitude of constrained catch success provided an initial indication of status that could be compared spatially and temporally. Second, biomass‐and‐abundance distributions were examined within dominant fish families. Large‐bodied species contributed most to biomass in low trophic positions, but small‐bodied counterparts were more abundant, following expected observations from systems with less human influence. However, biomass‐and‐abundance distributions became coupled for invertivores and predators, as small species and individuals were most represented. The shape and fit of regressions between asymptotic lengths and proportional landings identified drivers of coupled distributions. Polynomial fits highlighted that smaller‐bodied species were main components of the fishery, while linear fits suggested that larger‐bodied species were still dominant, and tolerant of current fishing pressure. Last, two indicators were used to identify management objectives for target fishes, skewness of size distributions and proportional contributions to landings. Significantly skewed size distributions existed for most target fishes, suggesting high density dependence and recruitment, and the potential for size‐based polices to achieve desirable fishery objectives. Meanwhile, the diminished and constrained contribution of many large species indicated their vulnerability despite non‐significant shifts in size. Catch quotas, gear limitations, or temporary restrictions may be more appropriate for sustaining these species. A framework is synthesized to interact with stakeholders and consider holistic management approaches for multispecies coral‐reef fisheries.